SEGMENTASI SATUAN KERJA DALAM RANGKA AKSELERASI PENYERAPAN ANGGARAN DAN MENDORONG EKONOMI REGIONAL - Widha Adinata; Bonny Adam; Ingelia Puspita (Direktorat Sistem Perbendaharaan, 2023)
The backlog of budget realization at the end of the year remains a persistent issue and has the potential to lead to budget inefficiencies. This study aims to address inefficiency problems in budget realization of spending units by utilizing the Segmentation, Targeting, and Positioning (STP) method. This involves processing budget realization performance data (MEBE and IKPA) as well as BPS GRDP data for the 2017-2021 period. The segmentation process, which utilizes K-means clustering, begins with variable selection through panel data regression to analyze the impacts on the regional economy, resulting in the identification of several clusters of spending units with similar characteristics. The targeting process determines which clusters are tergetted to increase budget realization and absorption in the current fiscal year. Finally, the positioning process involves rewarding high-performing clusters and assisting underperforming clusters to improve their performance. These efforts are expected to enhance the role of the DGT vertical unit in promoting regional economic growth.